2022
DOI: 10.1111/acem.14550
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the emergency department management of pediatric migraine by race, ethnicity, and language preference

Abstract: Background: There are disparities in pain management for children presenting to the emergency department (ED) according to their racial and ethnic backgrounds. It is not known if there are differences in the treatment of pain associated with pediatric migraines by race, ethnicity, and language for care (REaL). Methods:We analyzed treatment patterns and outcomes in our ED for acute migraine in pediatric patients by REaL. Retrospective data on treatments, length of stay (LOS), and charges were collected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Despite American Academy of Pediatrics and the American College of Emergency Physicians policies citing pediatric pain management as a priority and central component of patient‐ and family‐centered care, inadequate pain management remains prevalent in the ED 4 . To date, racial and ethnic disparities in pediatric pain management in the ED have been documented surrounding the treatment of bone fractures, appendicitis, migraines, and general pain management 2,3,5 . Collectively, data from this work indicate that, after controlling for clinical presentation and severity, children who are members of minoritized racial and ethnic groups are less likely to receive optimal pain care in the ED.…”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…Despite American Academy of Pediatrics and the American College of Emergency Physicians policies citing pediatric pain management as a priority and central component of patient‐ and family‐centered care, inadequate pain management remains prevalent in the ED 4 . To date, racial and ethnic disparities in pediatric pain management in the ED have been documented surrounding the treatment of bone fractures, appendicitis, migraines, and general pain management 2,3,5 . Collectively, data from this work indicate that, after controlling for clinical presentation and severity, children who are members of minoritized racial and ethnic groups are less likely to receive optimal pain care in the ED.…”
Section: Figurementioning
confidence: 88%
“…4 To date, racial and ethnic disparities in pediatric pain management in the ED have been documented surrounding the treatment of bone fractures, appendicitis, migraines, and general pain management. 2,3,5 Collectively, data from this work indicate that, after controlling for clinical presentation and severity, children who are members of minoritized racial and ethnic groups are less likely to receive optimal pain care in the ED. Millions of children require pain-related treatment in the ED each year and inadequate pain care is distressing and may contribute to negative short-and long-term clinical outcomes (e.g., heightened physiological pain responses and pain sensitivity, poorer recovery, increased pain and anxiety surrounding future Supervising Editor: Dr. Robert Cloutier.…”
mentioning
confidence: 79%
“… 18 , 19 This interaction deserves further exploration, especially given the frequently reported disparate care for Hispanic patients in the PED. 20 23 …”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that black patients were less likely to undergo tests in the ED (Zhang et al 2020a). Furthermore, disparities in racial/ethnic and language-based pain management in pediatric EDs were identified (Hartford et al 2022).…”
Section: Sociodemographic Disparities In Edmentioning
confidence: 99%